2011
DOI: 10.1523/jneurosci.5072-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Constancy and Variability in the Output of a Central Pattern Generator

Abstract: Experimental and corresponding modeling studies have demonstrated a 2–5 fold variation of intrinsic and synaptic parameters across animals, while functional output is maintained. These studies have led to the hypothesis that correlated, compensatory changes in particular parameters can at least partially explain the biological variability in parameters. Using the leech heartbeat CPG, we selected three different segmental motor neurons that fire in a functional phase progression but receive input from the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
90
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 23 publications
7
90
2
2
Order By: Relevance
“…In the pyloric network of the stomatogastric system, for example, the onset of the LP motoneuron is correlated to the synaptic conductance of each of its inputs from the pacemaker kernel, the AB/PD complex (Goaillard et al 2009). We do not see such correlations between single inputs and output phase in our system (Norris et al 2011), suggesting that there may be a more complex interaction between elements of the premotor synaptic conductance pattern and the heart motoneuron intrinsic properties.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the pyloric network of the stomatogastric system, for example, the onset of the LP motoneuron is correlated to the synaptic conductance of each of its inputs from the pacemaker kernel, the AB/PD complex (Goaillard et al 2009). We do not see such correlations between single inputs and output phase in our system (Norris et al 2011), suggesting that there may be a more complex interaction between elements of the premotor synaptic conductance pattern and the heart motoneuron intrinsic properties.…”
Section: Discussionmentioning
confidence: 62%
“…Across segments, heart motoneurons receiving the peristaltic pattern of synaptic input show phasing similar to the ensemble model. We do not attribute these discrepancies to experimental or procedural errors; furthermore, all of the appropriate inputs are accounted for in the segmental input patterns that were used in our model and dynamic clamp experiments (Norris et al 2011). A modulatory extrinsic input, acting on a cycle-by-cycle basis, may contribute to peristaltic phasing, but as of yet no such inputs have been identified in the leech.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on the pyloric network of the crustacean STN Schulz et al 2006;Schulz et al 2007) and on the inhibitory synaptic inputs to leech heart motoneurons (Norris et al 2007a;Norris et al 2011) has demonstrated a two-to fivefold animal-to-animal variability in intrinsic properties and/or in synaptic strengths, yet with functional circuit output. In this study, we uncovered an apparently much wider range of variability in synaptic strengths, with some connections in the core leech heartbeat CPG varying greater than sevenfold in strength across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…If the total complement of input onto an HN(4) oscillator interneuron is the critical factor in balancing the strengths of its inputs, then this lack of correlation may be due to the incompleteness of our comparison, c.f. Norris et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation